Phase-delay versus phase-rotation cells for circular polarization transmit arrays - application to Satellite Ka-Band Beam steering - Naseri, P. (2018)
Planar transmit arrays (TAs) have been an attractive solution as gain enhancers for various applications, e.g., satellite communications. The TA performance directly depends on its composing unit-cell characteristics. Planar unit cells can be categorized into two main types: phase-rotation (PR) and phase-delay (PD) cells. There is no hint in the literature about the relative merits of these two types of cells for circular polarization when assessing the final TA performance. This paper offers a systematic comparison between the cells’ working principles and analyzes their impacts on TA performance. Examples of a PR-based TA and a PD-based TA are designed for single-band wide-angle beam steering operating at the satellite Ka-band. They are evaluated by simulation and measurement to quantify performance differences. No previous work employed a PR TA for wide-angle beam steering. This paper shows that PR TA offers a filtering effect toward the cross-polarization component of the source. This leads to better axial ratio and combined 3 dB axial ratio and 3 dB gain bandwidth. However, PD cells are easier to design and insensitive to feed polarization. The analysis in this paper allows a more informed decision when selecting the unit-cell category for any given TA application.